Unilateral Adrenalectomy for Primary Bilateral Macronodular Adrenal Hyperplasia: Analysis of 71 Cases - Sheikh-Ahmad, Mohammad; Dickstein, Gabriel; Matter, Ibrahim; Shechner, Carmela; Bejar, Jacob; Reut, Maria; Sroka, Gideon; Laniado, Monica; Saiegh, Leonard (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective Primary bilateral macronodular adrenal hyperplasia (PBMAH) is characterized by benign bilateral enlarged adrenal masses, causing Cushing’s syndrome (CS). The aim of the current article is to define the role of unilateral adrenalectomy (UA) in treating patients with CS related to PBMAH.Methods A PubMed database search was conducted to identify articles reporting UA to treat PBMAH. We also report cases of PBMAH from our medical center treated by UA.Results A total number of 71 cases of PBMAH (62 cases reported in the literature and 9 cases from our center) are presented. Most patients were women (73.2%) and most UA involved the left side (64.3%). In most cases, the resected gland was the larger one. Following UA, 94.4% of cases had remission of hypercortisolism. Recurrence rate of CS was 19.4% and hypoadrenalism occurred in 29.6%. After UA, when the size of the remained adrenal gland was equal or greater than 3.5 cm, CS persisted in 21.4% of cases, and recurrence occurred in 27.3% of cases (after 20±9.2 months). However, when the size of the remained gland was less than 3.5 cm, CS resolved in all cases and recurrence occurred in 21.2% of cases after a long period (65.6±52.1 months). High levels of urinary free cortisol (UFC) were not correlated with post-surgical CS recurrence or persistence.Conclusions UA leads to beneficial outcomes in patients with CS related to PBMAH, also in cases with pre-surgical elevated UFC or contralateral large gland.
Keywords: unilateral; adrenal; surgery; adrenalectomy; macronodular; hyperplasia